The Clinical Spectrum and Management Patterns of Orbital Meningioma: A 6-Year Single-Institution Case Series from Indonesia - Anggia Dwi Kora; Mardijas Effendi; Ardizal Rahman (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Orbital meningiomas (OMs) are rare, complex tumors whose clinical course and management are debated. Data from Southeast Asian populations, particularly Indonesia, is scarce. This study aims to define the clinical spectrum, radiological features, and management trends of OMs at a single Indonesian tertiary referral center, with a focus on hormonal factors in a predominantly female cohort. Methods: A retrospective, descriptive case series was conducted on all patients diagnosed with orbital meningioma at Dr. M. Djamil General Hospital, Padang, Indonesia, from January 2018 to December 2023. Data on demographics, detailed clinical presentation (visual acuity, proptosis, extraocular movement), radiological findings (location, size, hyperostosis), and hormonal risk factors were collected. Management strategies, histopathological results (WHO grade), and follow-up outcomes were analyzed. Results: Twenty patients were included, with a significant female predominance (n=16, 80%; F:M ratio 4:1). The median age at diagnosis was 47 years (range 28-71). A strong association with hormonal factors was noted; 50% (8/16) of female patients had a history of exogenous hormonal contraceptive use. The most common presenting symptoms were progressive proptosis (n=15, 75%) and visual loss (n=12, 60%). The mean proptosis was 5.5 ± 2.1 mm. The most frequent tumor location was retrobulbar (intraconal) (n=11, 55%), followed by optic nerve sheath (n=5, 25%). A multidisciplinary, conservative-led approach was the primary management strategy, with 75% (n=15) of patients managed with active observation and neurosurgical consultation. Surgical intervention was performed in 25% (n=5) of cases, primarily for severe symptoms or aggressive radiological features. Histopathology (n=5) confirmed WHO Grade I in four cases (80%) and WHO Grade II (atypical) in one case (20%). Conclusion: Orbital meningiomas in this Indonesian cohort demonstrate a striking female predominance and a strong association with hormonal contraceptive use, suggesting a significant role for hormonal pathways in their pathophysiology. The management paradigm has shifted towards a multidisciplinary, observation-first approach, reserving surgical intervention for cases with documented progression, severe vision loss, or high-grade pathological features.